Placental location and fetomaternal outcome: a prospective study - Aggarwal, Prachi; Chauhan, Nidhi; Agarwal, Anchal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The placental position within the uterus can significantly influence pregnancy outcomes, impacting maternal and fetal well-being. It has been associated with complications such as preeclampsia, intrauterine growth restriction (IUGR), and premature rupture of membranes (PROM). Understanding how different placental locations affect pregnancy outcomes is essential for optimizing clinical management and improving maternal and neonatal health. Objective of this study was to assess the effect of placental location on maternal and fetal outcomes. Methods: This prospective study was conducted in the Department of Obstetrics and Gynaecology, Himalayan Institute of Medical Sciences, Dehradun, over 12 months from June 2023 to May 2024. 120 pregnant women with singleton pregnancies over 18 weeks of gestation were recruited. After determining placental location via ultrasonography, the participants were divided into three groups: anterior (n=53), posterior (n=46), and lateral (n=21). Maternal and fetal outcomes were assessed and analysed using SPSS software (version 23), with a p-value of less than 0.05, considered statistically significant. Results: The most common placental location was anterior (44.1%), followed by posterior (38.3%) and lateral (17.5%). A significant association was observed between lateral placental location and hypertensive disorders including per-eclampsia (p=0.01), while anterior placental location was significantly associated with a higher incidence of PPROM/PROM (p=0.002). Regarding fetal outcomes, lateral placentation was significantly associated with IUGR (p=0.01). Although NICU admission rates were higher in the anterior placental group (35.8%), no significant correlation was found between placental location and neonatal outcomes. Conclusions: Placental location, particularly lateral positioning, is significantly associated with adverse maternal and fetal outcomes, including hypertensive disorders and IUGR. Anterior placental location showed a strong association with PPROM/PROM. Further research is necessary to confirm these findings and refine clinical management strategies for pregnancies with abnormal placental locations.